HYPOGLYCEMIC, ANTI-INFLAMMATORY EFFECT OF PORANG (AMORPHOPHALLUS ONCHOPYLLUS) ON ALLOXAN-INDUCED DIABETIC RATS - Young, Andre; Novita, Bernadette Dian; Ricardo, Evan; Dewi, I.G.A.P.D; Amadeo, Jovan; Dewi, Sianty; Tahalele, Paul (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Introduction: Iles-iles / Porang is a tuber-producing plant that is commonly found in Indonesia. One of the most sought after content from Porang is Glucomannan. One of Porang’s health benefit is related to the effect of lowering blood glucose levels because it can prevent glucose absorption. These benefit is interesting to study because there has been no research linking the use of Porang to reduce inflammatory process in hyperglycmic conditions. Purpose: This study aims to analyze the anti-inflammatory, anti-oxidant and hypoglycemis effects of Glucomannan from Porang (Amorphophallus onchophyllus) extract in experimental animals. Method: The research design was a true experimental post-test only control group with random sampling to determine 5 white rats into the normal group, positive control group, negative control group and treatment 1, 2 and 3. The positive control group received Acarbose therapy thile the negative control group received carboxy-methyl-cellulose (CMC) therapy. This study used Porang extract (Amorphophallus onchophyllus) with concentrations of 200, 400 and 800 mg/Kg in hyperglycemic white rats that had been induced by Aloxan. The study was conducte for 50 days and then blood and serum samples were taken to assess the effect of hypoglycemia, anti-inflammatory and anti-oxidant using blood glucose, Malondialdehyde and C-reactiveprotein (CRP) measurement. Result and Discussion: The results showed no significant difference between the groups of rats receiving Porang extract and the positive and negative control groups. However, the MDA levels after 50 days of intervention between the negative control group and the therapy with doses of 200, 400 and 800 mg/Kg showed significant differences. Similarly found for blood glucose levels after intervention between negative control group and the 200 and 400 mg/Kg therapy group. This results may be caused by the type of Porang used, the form of the Porang and the concentration level of the Porang extract. Conclusion: Porang with the type of Amorphophallus onchophyllus can’t be used directly, but requires further processing to obtain the active substance Glucomannan.